Factors influencing oral health behaviours, access and delivery of dental care for autistic children and adolescents: A mixed‐methods systematic review. (18th June 2022) - Erwin, Jo; Paisi, Martha; Neill, Sarah; Burns, Lorna; Vassallo, Isaac; Nelder, Abigail; Facenfield, Jemma; Devalia, Urshla; Vassallo, Tara; Witton, Robert
Abstract: Background: Autistic children and young people (CYP) experience oral health (OH) inequalities. They are at high risk of dental disease and show significant levels of unmet need in relation to OH and access to dental care. Aim: This study aimed to gather evidence on the factors that influence OH behaviours, access to and delivery of dental care for autistic CYP. Design: This was a mixed‐methods narrative systematic review. Data Sources: Embase, Web of Science, Dentistry & Oral Sciences Source, MEDLINE, Psychinfo, Scopus, CINAHL, SocINDEX and grey literature were the data sources for this study. Review Methods: A systematic search was conducted for qualitative, quantitative and mixed‐methods research studies from countries with a High Development Index that related to OH behaviours, access to and delivery of dental care for autistic CYP. Results were analysed using narrative synthesis. Results: From 59 eligible studies, 9 themes were generated: (1) affordability and accessibility; (2) autism‐related factors and cognitive or motor skill differences; (3) the dental environment; (4) managing CYP's behaviour; (5) responding and adapting to the needs of the autistic CYP and their parent/carer; (6) attitude of dental health professionals (DHPs) towards autistic CYP and their parents/carers; (7) knowledge of how to care for and support CYP's OH; (8) empowerment of parents/carers and collaboration with DHPs; and (9) communication and building rapport. Conclusion: The adoption of healthy OH behaviours and access to dental care by autistic CYP is impacted by a range of factors including those intrinsically related to a diagnosis of autism, for example, communication and those often associated with autism, for example, sensory sensitivities. Access to better OH and dental care can be facilitated by responding to the individual needs of autistic CYP through accommodation, education and adaptation. This necessitates greater awareness and knowledge of autism amongst DHPs and the provision of appropriate services. More methodologically robust intervention studies are needed to identify effective ways to support autistic CYP in achieving good OH and access to dental care. Patient and Public Contribution: The review protocol was developed with members of the project patient and public involvement group who provided the autistic voice, contributing to the interpretation of the review findings and writing of the manuscript.